Radionuclides level and its radiation hazard index in some drinks consumed in central zone of Malaysia - Tawalbeh, A.A.; Samat, S.B; Yasir, M.S. (Universiti Kebangsaan Malaysia, 2013)
Fifty three samples of different types of imported and locally produced drinks consumed in the central zone of Malaysia were analyzed using gamma-ray spectrometry system equipped with a high purity germanium (HPGe) detector. The activity concentrations of the natural radionuclides 238U, 232Th and 40K present in the studied samples were measured and the radium equivalent activities Raeq were calculated. In addition, the radiation hazard index (HI) was calculated. The average concentrations of 238U, 232Th and 40K were 0.69 ± 7×10¯4 , 1.3 ± 8×10¯4 and 20.52 ± 6×10¯4 Bq/Kg, respectively. The values of Raeq were between 0.002 and 10.0 Bq/kg. The HI were between 0.002 and 0.03, which is below one (the higher limit of HI). The results obtained were compared to the standard accepted international values and found to be within the acceptable limits.